Guggulusome - A Novel Vesicular Carriers for Enhanced Transdermal Delivery - Vivek Dave; Sachdev Yadav; Swapnil Sharma; Nitesh Panwar (College of Pharmacy University of Baghdad, 2017)
The present work describes guggul as a novel carrier for some anti-inflammatory drugs. Guggulusomes containing different concentration of guggul with aceclofenac were prepared by sonication method and characterized for vesicle shape, size, size-distribution, pH, viscosity, spread ability, homogeneity, and accelerated stability in-vitro drug permeation through mouse skin. The vesicles exhibited an entrapment efficiency of 93.2 Â± 12%, vesicle size of 0.769 Â± 3Î¼m and a zeta potential of - 6.21mV. In vitro drug release was analyzed using Franzâ€™s diffusion cells. The cumulative release of the guggulusomes gel (G2) was 75.8% in 18 hrs, which is greater than that all the gel formulation. The stability profile of prepared system assessed for 45 days. The vesicular suspension was kept in sealed vials (10ml) at 4 Â± 2ÂºC and at room temperature for 45 days no change was showned in entrapment efficiency. The optimized guggulusomes formulation showed transdermal flux 216.1Î¼g/cmÂ²/hr. The result advocates the potential of guggulusomes formulation to treat diseases where facilitated penetration of the drug into muscle and synovial fluid is desirable. In the end of the tests guggulusomes gel G2 with carbopol 934K was the most stable. The paw edema and percentage inhibition of carrageenan-induced paw edema in rats treated with aceclofenac guggulusomes gels and commercial formulation of aceclofenac gel marketed gel. The formulation G2 were devoid of any irritation potential and no edema formation was observed in any case. Irritation score for aceclofenac guggulusomes gels was zero, which indicated its acceptability for topical administration. Keywords:  Aceclofenac, Gel, Carbopol, Guggulu carrier.